EFFECT OF SALICYLLC ACID FOLIAR APPLICATION ON PHYTOCHEMICAL COMPOSITION, ANTIOXIDANT AND ANTIMICROBIAL ACTIVITY OF SILYBUM MARIANUM - Rad, Z. Mahmoudi; Nourafcan, H.; Mohebalipour, N.; Assadi, A.; Jamshidi, S. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
Silybum marianum (L.), is an important herbal medicine. Silymarin, the active component obtained from its edible seeds, is known for its antioxidant and antimicrobial activity. This research was aimed to study the effect of foliar application of salicylic acid (SA) at four concentrations of 1250, 2500, 5000 and 10000 μmol l-1 on the improvement of phytochemical composition, antioxidant and antimicrobial activity. Significant increase was found in the content of silibinin, silybin A and silybin B in plants treated with increasing concentrations of salicylic acid. The antioxidant activity was improved with increasing the SA concentration reaching the highest amount under 5000 μmol l-1 SA treatment (p < 0.05). Irrespective to the bacterial strain, an increasing pattern in the amount of antibacterial activity was found by increasing SA concentration. The study suggest that treatments with medium doses of SA could be a promising way to improve the health beneficial flavonolignans compounds of Silybum marianum resulting in a higher antioxidant and antimicrobial activity. Nevertheless, it should be considered that the responses to SA are highly concentration dependent and application of higher concentrations can have an adverse effect by triggering a hyper sensitive cell death pathway.